2008
DOI: 10.1101/gr.076653.108
|View full text |Cite
|
Sign up to set email alerts
|

HBEGF, SRA1, and IK: Three cosegregating genes as determinants of cardiomyopathy

Abstract: Human dilated cardiomyopathy (DCM), a disorder of the cardiac muscle, causes considerable morbidity and mortality and is one of the major causes of sudden cardiac death. Genetic factors play a role in the etiology and pathogenesis of DCM. Disease-associated genetic variations identified to date have been identified in single families or single sporadic patients and explain a minority of the etiology of DCM. We show that a 600-kb region of linkage disequilibrium (LD) on 5q31.2-3, harboring multiple genes, is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 51 publications
2
63
0
1
Order By: Relevance
“…In vivo experiments showed that a decrease in SRA expression lead to a phenotype of myocardial contractile dysfunction in a zebrafish model [6], whereas an increase in mouse mammary gland stimulated proliferation and apoptosis [7]. Altogether, SRA is suspected to participate in normal and pathological events such as tissue differentiation and tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo experiments showed that a decrease in SRA expression lead to a phenotype of myocardial contractile dysfunction in a zebrafish model [6], whereas an increase in mouse mammary gland stimulated proliferation and apoptosis [7]. Altogether, SRA is suspected to participate in normal and pathological events such as tissue differentiation and tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…This region contains a number of genes, three of which (HBEGF, SRA1 and IK) were knocked down by MO in zebrafish embryos and shown to induce DCM [92].…”
Section: The Genetics Of Cardiovascular Disease 193mentioning
confidence: 99%
“…Indeed, a recent study has Table 1. shown that knocking down SRA gene led to myocardial contractile dysfunction in zebrafish, linking for the first time SRA and heart diseases [15]. The wide range of transcription factors identified as interacting with SRAP suggests that many normal and pathogenic events might involve this newly described protein.…”
Section: Srap Interacts With Multiple Transcription Factorsmentioning
confidence: 99%